Elder perspectives: leveraging digital tools in language revival initiatives - Bishop, Melissa (2019)
Elders are held in high regard in First Nations, Metis, and Inuit (FNMI) communities. They are the intergenerational transmitters of ancestral language and Indigenous knowledge. Without language revival initiatives, ancestral languages in FNMI communities are at risk of extinction. Leveraging digital technologies while collaborating with Elders can support revival initiatives. Through semi-structured interviews and qualitative analysis, this study addresses how three Elders who use technology in their ancestral language teaching (1) describe the benefits, drawbacks, and preferences of technology; (2) reveal the accuracy with which cultural knowledge is imparted through technology; and (3) view the impact of technology on their role as traditional knowledge keepers and intergenerational language transmitters? Findings suggest that while Elders acknowledge the benefits when leveraging digital tools in language revival initiatives, they have concerns about technology’s potential negative impacts on relationality [culture, spirituality, and medicine practices], a concept I have termed guarded optimism. University of Ontario Institute of Technology